The relation between the geometrical thinking level and the spatial ability level among female secondary students in Al-Madinah Al-Munawarh, Kingdom of Saudi Arabia - Al - Juhani, Aisha Jumahiaan Atallah (Arab Journal for Sciences and Research Publishing, 2016)
The study  aimed  to find out the relation between the geometrical thinking level and the spatial  ability level among female secondary students in Al-Madinah Al-Munawarh, Kingdom of Saudi Arabia. The researcher chose a random sample of (60) Student from secondary stage, scientific stream.  In addition, researcher employed descriptive research design through developing a test to examine the spatial ability level and using (Van Hiele) test to measure the geometrical thinking level because of its suitability for the environment of Kingdom of Saudi Arabia. The frequencies, percentages, and Pearson Correlation Coefficient were conducted in the statistical analysis by the researcher.   The results of the current study were the following: The geometrical thinking level was not high and the majority of participants were in the second level of geometrical thinking which is the analytical level. And the spatial ability level was not high and the majority of participants were in the first level spatial ability which is the spatial consciousness level. The study also showed a positive statistical relation between geometrical thinking level and the spatial ability level. The researcher suggested some recommendations at the end of research such as paying attention to develop the geometrical thinking level among the participants through using various teaching methods as directed discovery to solve problems, keeping away the routine performance which depends on the memorization of theories, and using the activities which improves the spatial ability level.
Keywords: level of engineering thinking; spatial ability level; Medina; High school students